State Park of the Ipiranga Fountains: important conservation unit for the protection of the bryoflora from the Atlantic forest in São Paulo city, Brazil - Visnadi, Sandra Regina (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
The State Park of the Ipiranga Fountains (PEFI) is the third largest reserve of native forest in the municipality of São Paulo. The paper shows the diversity of bryophytes in PEFI, listing 266 species for this park, whose material totalizes 1,818 exsiccate from Herbarium of the São Paulo Botanical Institute (SP). The bryoflora from PEFI is typical of the hillside Atlantic Forest of the São Paulo state. The high similarity of the antropic and forest areas of the PEFI shows the afforestation of the antropic areas and the maintenance of the forest areas in their surroundings minimize the effects of the deforestation over the bryoflora. The Atlantic forest that covers PEFI emphasizes the importance of the park in the protection of the bryophytes flora from this ecosystem. The PEFI also stands out by the new records for São Paulo [Brachythecium plumosum (Hedw.) Schimp., Lepidopilidium plebejum (Müll. Hal.) Sehnem, Riccia enyae Jovet-Ast], by the occurrence of species, which in Brazil is restricted to the São Paulo state [Bryum challaense Broth., Cololejeunea microscopica (Taylor) Schiffn., Drepanolejeunea subdissitifolia Herzog, Eurhynchium hians (Hedw.) Sande Lac., Lejeunea lamacerina (Steph.) Schiffn., Lepidolejeunea bidentula (J.B. Jack & Steph.) R.M. Schust.] and of 16 endemic species from Brazil.